Partition member for total heat exchange element, total heat exchange element using the same, and method for manufacturing partition member for total heat exchange element
A partition member with a hydrophobic porous base and hydrophilic coating addresses the challenge of thinness and efficiency, enabling multiple layers for enhanced heat exchange performance.
Patent Information
- Application Number
- JP2024107760
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2023-07-06
- Filing Date
- 2024-07-03
- Publication Date
- 2025-01-20
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
Existing partition members for total heat exchange elements are difficult to make thinner while maintaining high heat exchange efficiency, air permeability, and moisture permeability, limiting the number of stackable layers.
A partition member comprising a hydrophobic porous base material with a hydrophilic material attached, having a thickness of 5 μm to 30 μm, an air permeability of 10,000 seconds or more, and a moisture permeability of 2500 g/m², achieved by coating a hydrophilic material onto the base material with controlled adhesion and drying.
The partition member is extremely thin, lightweight, and enhances heat exchange efficiency with high air and moisture permeability, allowing for more layers to be stacked, thus improving overall heat exchange performance.
Smart Images

Figure 2025010103000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to a partition member for a total heat exchange element, a total heat exchange element including the same, and a method for manufacturing the partition member for a total heat exchange element. [Background technology]
[0002] Conventionally, a heat exchange ventilation device (heat exchanger) that exchanges heat between the intake air and the exhaust air during ventilation has been proposed as a device that can ventilate without impairing the cooling or heating effect. A total heat exchanger is widely used for this heat exchanger, which is made by stacking multiple partition members (liners) via spacing members, dividing the intake air path that introduces outdoor air into the room and the exhaust air path that exhausts indoor air to the outside, and simultaneously exchanges sensible heat (temperature) and latent heat (humidity).
[0003] For example, in winter, outdoor air as supply air and indoor air as exhaust air are guided into each flow path separated by a spacing member. At this time, the supply air and exhaust air exchange temperature and humidity through the partition member. The partition member through which heat exchange occurs has moisture permeability that allows water vapor to pass but not air. The partition member also has gas shielding properties due to the isolation between the supply air and exhaust air. As a result, the supply air is heated and humidified before being supplied to the room, and the exhaust air is cooled and dehumidified before being discharged outside. The partition member has both moisture permeability and gas shielding properties, thereby achieving ventilation through total heat exchange. Such partition members need to have both heat conductivity and moisture permeability, and therefore in many cases, paper containing natural pulp as a main component, such as glassine paper, is used as a paper base material (Patent Document 1).
[0004] Furthermore, in recent years, attempts have been made to apply cellulose nanofibers, which have gas barrier properties, to partition members (Patent Document 2). [Prior art documents] [Patent documents]
[0005] [Patent Document 1] Patent No. 4252892 [Patent Document 2] Patent Publication No. 2021-155865 Summary of the Invention [Problem to be solved by the invention]
[0006] In light of the need to combat global warming and conserve energy, total heat exchange elements have been attracting attention. In order to further improve the heat exchange efficiency of total heat exchange elements, it is believed that it would be effective to make the partition members thinner than ever before and to increase the number of stacked layers of the total heat exchange element. However, this has been difficult to achieve with the partition members described in Patent Documents 1 and 2. [Means for solving the problem]
[0007] The inventors conducted intensive research in order to provide a partition member for a total heat exchanger that has high air permeability and moisture permeability, excellent carbon dioxide barrier properties, and is extremely thin, and as a result, they discovered and invented a new partition member for a total heat exchange element that uses a hydrophobic porous substrate and a hydrophilic material. That is, the present invention provides the following: <1> ~ <12> Regarding. <1> A partition member for a total heat exchange element comprising a hydrophobic porous substrate and a hydrophilic material, the hydrophilic material is attached to the hydrophobic porous substrate; The thickness of the hydrophobic porous substrate is 5 μm or more and 30 μm or less, The amount of the hydrophilic material attached is 0.01 g / m 2 More than 8g / m 2 is as follows: Surface density of 30g / m as a partition material for total heat exchange elements 2 The following describes a partition member for a total heat exchange element having an air permeability of 10,000 seconds or more. <2> The hydrophobic porous substrate has an air permeability of 1000 seconds or less. <1> The partition member for a total heat exchange element according to claim 1. <3> The hydrophilic material is coated on the hydrophobic porous substrate. <1> or <2> The partition member for a total heat exchange element according to claim 1. <4> The moisture permeability of the partition member for the total heat exchange element is 2500 g / m2 -24 hours or more <1> ~ <3> 2. A partition member for a total heat exchange element according to claim 1 . <5> <1> ~ <4> A total heat exchange element partition member according to any one of claims 1 to 4, a spacer member arranged between the total heat exchange element partition members and spaced apart from the adjacent total heat exchange element partition members; A total heat exchange element having a first air flow path formed by a partition member for the total heat exchange element and the spacing member provided thereon, and a second air flow path formed by a partition member for the total heat exchange element that forms the first air flow path and the spacing member provided thereon. <6> A hydrophobic porous substrate having a thickness of 5 μm or more and 30 μm or less is provided with a hydrophilic material attached in an amount of 0.01 g / m on at least one surface thereof. 2 More than 8g / m 2 The coating liquid containing the hydrophilic material is applied and dried so that the surface density is 30 g / m 2 The following describes a method for producing a partition member for a total heat exchange element having an air permeability of 10,000 seconds or more. <7> The hydrophobic porous substrate has an air permeability of 1000 seconds or less. <6> A method for producing the partition member for the total heat exchange element described above. <8> The moisture permeability of the partition member for the total heat exchange element is 2500 g / m 2 -24 hours or more <6> or <7> A method for producing the partition member for a total heat exchange element according to claim 1. <9> The coating fluid is applied using a blade coater, bar coater, or rod coater. <6> ~ <8> 2. A method for producing the partition member for a total heat exchange element according to claim 1 . <10> Surface temperature must be below 80℃ <6> ~ <9> 2. A method for producing the partition member for a total heat exchange element according to claim 1 . <11> The coating liquid contains a surfactant <6> ~ <10> 2. A method for producing the partition member for a total heat exchange element according to claim 1 . <12> After the hydrophobic porous substrate is subjected to a surface hydrophilization treatment, the coating liquid is applied thereto. <6> ~ <11> 2. A method for producing the partition member for a total heat exchange element according to claim 1 . Effect of the Invention
[0008] According to the present invention, there are provided a partition member for a total heat exchange element which is lightweight, extremely thin, and has high heat exchange efficiency, a total heat exchange element using the same, and a method for manufacturing a partition member for a total heat exchange element. [Brief description of the drawings]
[0009] [Figure 1] FIG. 1 is a schematic diagram illustrating the structure of a total heat exchange element. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0010] [Partition material for total heat exchange element] The partition member for a total heat exchange element of the present invention (hereinafter also referred to as the partition member) is a partition member for a total heat exchange element comprising a hydrophobic porous substrate and a hydrophilic material, the hydrophilic material being attached to the hydrophobic porous substrate, the thickness of the hydrophobic porous substrate being 5 μm or more and 30 μm or less, and the amount of the hydrophilic material attached being 0.01 g / m 2 More than 8g / m 2 and the surface density as a partition member for a total heat exchange element is 30 g / m or less. 2 The following is a partition member for a total heat exchange element having an air permeability of 10,000 seconds or more.
[0011] In the present invention, the surface density of the partition member is a value obtained by measuring the weight per unit area. The surface density of the partition member is preferably 30 g / m 2 Less than 26g / m 2 The following is the result. In the present invention, the "air permeability" is a value measured in accordance with the Oken air permeability method of JAPAN TAPPI paper pulp testing method No. 5-2:2000. The partition member for a total heat exchange element of the present invention preferably has an air permeability of 40,000 seconds or more.
[0012] The hydrophobic porous substrate to be used is not particularly limited as long as it has a thickness of 5 μm or more and 30 μm or less. A preferred thickness is 10 to 25 μm. By setting the thickness to be equal to or more than the lower limit, the strength as a partition member is maintained, and by setting the thickness to be equal to or less than the upper limit, the heat exchange efficiency of sensible heat (temperature) is increased and weight reduction is possible. The thickness is a value measured in accordance with JIS P 8118:2014.
[0013] By attaching a hydrophilic material to a hydrophobic porous substrate, it is possible to increase the air permeability and improve the gas barrier properties without significantly impairing the moisture permeability. 2 More than 8g / m 2 When the amount of the hydrophilic material is less than 5 g / m, the pores of the substrate can be blocked with the hydrophilic material, and the decrease in moisture permeability can be suppressed. When the amount of the hydrophilic material attached is large, the gas barrier property is excellent, but the moisture permeability tends to be impaired. 2 On the other hand, if the amount of the hydrophilic material attached is small, sufficient gas barrier properties tend not to be obtained, and the amount of attachment is preferably 0.03 g / m or less. 2 More preferably, it is equal to or greater than this. The amount of hydrophilic material applied can be rephrased as the amount of hydrophilic material applied, as will be described in detail below.
[0014] The surface density of the partition material for the total heat exchange element is 30 g / m 2 In order to achieve the above, the areal density of the hydrophobic porous substrate must be 29 g / m 2 It is preferable that the thickness is 25 g / m or less. 2 More preferably, it is 20 g / m or less. 2 The lower limit is not particularly limited, and is 2 g / m or less. 2 More preferably, it is 5 g / m 2 That's all.
[0015] A hydrophobic porous substrate can be made lighter because the substrate is hydrophobic. For example, when a hydrophilic porous substrate such as paper is used, a large amount of hydrophilic material must be applied to improve the gas barrier property, making it difficult to make the substrate lighter.
[0016] In addition, since the substrate is porous, it allows for latent heat (humidity) heat exchange. As a guide for porosity, the air permeability of the hydrophobic porous substrate is about 1000 seconds or less, preferably 500 seconds or less. There is no particular limit to the lower limit of the air permeability, but it is 10 seconds or more, preferably 30 seconds or more, and more preferably 50 seconds or more. For example, films or nonwoven fabrics made of thermoplastic resins such as polyolefin and polyester, and having an air permeability of 1000 seconds or less, preferably 500 seconds or less, can be used.
[0017] In addition, the moisture permeability of the partition material for the total heat exchange element is 2500g / m 2 -24 hours or more is preferable. In the present invention, the moisture permeability is a value measured in accordance with JIS Z 0208:1976.
[0018] The hydrophilic material is not particularly limited as long as it is a material that forms a film by adhering to a hydrophobic porous substrate and exhibits gas barrier properties. Examples include polymeric polysaccharides such as cellulose, chitin, chitosan, and carboxymethyl cellulose, and their derivatives, polyvinyl alcohol and its derivatives, and ethylene-vinyl alcohol copolymers and their derivatives. For example, polymeric polysaccharides have a molecular structure with many hydroxyl groups (-OH), so they have a moisture absorbing effect and the film formed has gas barrier properties. Polyvinyl alcohol also has a molecular structure with many hydroxyl groups (-OH groups), and has excellent film properties. Among them, fibrous materials are preferred, fine fibers of polymeric polysaccharides are more preferred, and fine cellulose fibers are particularly preferred. Fine cellulose fibers are preferred because they form a dense structure when attached by coating and drying, and therefore have excellent gas barrier properties.
[0019] The fine cellulose fibers preferably have a fiber width of 1 to 1000 nm. Among them, from the viewpoint of gas barrier properties, the fiber width is preferably 1 to 500 nm, more preferably 1 to 100 nm, further preferably 1 to 30 nm, and particularly preferably 1 to 10 nm. By making the fiber width of the fine cellulose fibers 1 nm or more, dissolution of the cellulose molecules in water is suppressed, and the effect of improving the air permeability and moisture permeability of the fine cellulose fibers is easily achieved.
[0020] The average fiber width of cellulose fibers is measured using an electron microscope as follows. First, prepare an aqueous suspension of cellulose fibers with a concentration of 0.05% by mass to 0.1% by mass, and cast this suspension onto a hydrophilized carbon film-coated grid to prepare a sample for TEM observation. If the sample contains wide fibers, it may be cast onto glass and the SEM image of the surface may be observed. Next, the image is observed using an electron microscope at a magnification of 1,000x, 5,000x, 10,000x, or 50,000x depending on the width of the fiber to be observed, with the sample, observation conditions, and magnification adjusted to satisfy the following conditions. (1) A straight line X is drawn at any point within the observed image, and 20 or more fibers intersect with the straight line X. (2) Within the same image, draw a line Y that intersects the line perpendicularly, and have 20 or more fibers intersect with the line Y. For observation images that satisfy the above conditions, the width of the fibers intersecting with the lines X and Y is visually read. In this manner, three or more sets of observation images of at least the surface portions that do not overlap each other are obtained. Next, for each image, the width of the fibers intersecting with the lines X and Y is read. In this manner, the fiber widths of at least 20 fibers x 2 x 3 = 120 fibers are read. The average fiber width is the average value of the fiber widths of the read cellulose fibers.
[0021] The fiber length of the fine cellulose fibers is not particularly limited, but is preferably 0.1 μm or more, and preferably 1,000 μm or less, more preferably 800 μm or less, and even more preferably 600 μm or less. By setting the fiber length of the fine cellulose fibers within the above range, destruction of the crystalline regions of the fine cellulose fibers can be suppressed. In addition, it is possible to set the slurry viscosity of the fine cellulose fibers within an appropriate range, making it easy to form a fiber layer. The fiber length of the fine cellulose fibers can be determined by image analysis using, for example, TEM, SEM, or AFM.
[0022] The axial ratio (fiber length / fiber width) of the fine cellulose fibers is not particularly limited, but is preferably at least 20, more preferably at least 50, and is preferably at most 10,000, more preferably at most 1,000. By setting the axial ratio within the above range, a slurry viscosity suitable for forming a fiber layer can be obtained.
[0023] In the present invention, it is preferable that at least one of an ionic group and a nonionic group is introduced into the fine cellulose fiber. In addition, the ionic group and the nonionic group are preferably hydrophilic groups. From the viewpoint of improving the dispersibility of the fiber in the dispersion medium and increasing the defibration efficiency in the defibration treatment, it is more preferable that the fine cellulose fiber has an ionic group. The ionic group may include either one or both of an anionic group and a cationic group. In the present invention, it is particularly preferable that the ionic group has an anionic group. The anionic group is preferably at least one selected from a phosphate group or a group derived from a phosphate group, a phosphite group or a group derived from a phosphite group, a carboxy group or a group derived from a carboxy group, and a sulfonic acid group or a group derived from a sulfonic acid group.
[0024] The partition member for a total heat exchange element of the present invention is a partition member for a total heat exchange element comprising a hydrophobic porous substrate and a hydrophilic material, the hydrophilic material being attached to the hydrophobic porous substrate, the thickness of the hydrophobic porous substrate being 5 μm or more and 30 μm or less, and the amount of the hydrophilic material attached being 0.01 g / m 2 More than 8g / m 2 and the surface density as a partition member for a total heat exchange element is 30 g / m or less. 2 The air permeability is 10,000 seconds or more. Therefore, the partition member for a total heat exchanger has high air permeability and moisture permeability, and is extremely thin and has excellent carbon dioxide barrier properties. In addition, the partition member is lightweight, which allows the number of stacked layers of the total heat exchange element to be increased.
[0025] [Manufacturing method of partition members] The present invention provides a method for producing a hydrophobic porous substrate having a thickness of 5 μm or more and 30 μm or less, with a hydrophilic material attached in an amount of 0.01 g / m on at least one surface of the substrate. 2 More than 8g / m 2 The coating liquid containing the hydrophilic material is applied and dried so that the surface density is 30 g / m 2 The following is a method for producing a partition member for a total heat exchange element having an air permeability of 10,000 seconds or more.
[0026] Details of the hydrophobic porous substrate and the hydrophilic material are as described above. The hydrophilic resin is applied by coating. For example, a coating liquid containing a hydrophilic material is applied to the hydrophobic porous substrate, followed by drying. Water is preferably used as the solvent for the coating liquid. A known coating machine can be used for the coating method, and is not particularly limited. Blade coaters, bar coaters, curtain coaters, die coaters, air knife coaters, roll coaters, etc. can be used. Among them, blade coaters and bar coaters are preferred because the pressing force of the blade or bar during coating causes the coating liquid to penetrate into the pores of the porous substrate. For drying, a dryer attached to the coating machine can be used. The drying temperature is preferably a surface temperature of 90°C or less, more preferably 80°C or less, and even more preferably 70°C or less. Drying at a high temperature may cause bumping of the coating liquid. In addition, drying at a low temperature can suppress the occurrence of wrinkles in the porous substrate. Furthermore, when coating, it is preferable to subject the surface of the substrate to a corona discharge treatment in advance, since this makes it easier to form a uniform coating film even when the amount of adhesion is small.
[0027] The amount of hydrophilic material attached is 0.01g / m 2 More than 8g / m 2 When the amount of the hydrophilic material is less than 5 g / m, the pores of the substrate can be blocked with the hydrophilic material, and the decrease in moisture permeability can be suppressed. When the amount of the hydrophilic material attached is large, the gas barrier property is excellent, but the moisture permeability tends to be impaired. 2 On the other hand, if the amount of the hydrophilic material attached is small, sufficient gas barrier properties tend not to be obtained, and the amount of attachment is preferably 0.03 g / m or less. 2 Applying a hydrophilic material by coating is preferable because it is possible to increase the moisture permeability, possibly because the hydrophilic material penetrates not only into the surface of the hydrophobic porous substrate but also into the interior of the pores.
[0028] When applying a coating liquid containing a hydrophilic material to a hydrophobic porous substrate, if the substrate repels the coating liquid, it is advisable to add a surfactant, a wetting agent, a leveling agent, etc. to the coating liquid, or to subject the substrate to a surface hydrophilization treatment such as corona discharge treatment in advance, or to use these in combination. If repelling occurs during application, it tends not to be possible to obtain a partition member for a total heat exchange element having an air permeability of 10,000 seconds or more.
[0029] Since the amount of fine fibers of polymeric polysaccharide attached to the partition member of the present invention is small, latent heat (humidity) heat exchange is performed even without the attachment of a moisture absorbent, but a moisture absorbent may be blended to further increase moisture permeability. Examples of moisture absorbents include inorganic acid salts, organic acid salts, polyhydric alcohols, and ureas. For example, inorganic acid salts include lithium chloride, calcium chloride, and magnesium chloride. Examples of organic acid salts include sodium lactate, calcium lactate, and sodium pyrrolidone carboxylate. Examples of polyhydric alcohols include glycerin, ethylene glycol, triethylene glycol, and polyglycerin. Examples of ureas include urea and hydroxyethyl urea.
[0030] In addition, the coating liquid may contain auxiliary agents such as preservatives, antifungal agents, flame retardants, viscosity adjusters, pH adjusters, colorants, storage improvers, and polymer resins, as long as the effects of the present invention are not impaired.
[0031] When applying the coating solution containing the hydrophilic material, the amount of the coating liquid is adjusted so that the resulting partition member for a total heat exchange element has an air permeability of 10,000 seconds or more. 2 It is preferable to adjust the amount of adhesion so that it lasts for 24 hours or more.
[0032] As described above, since the coating liquid containing the hydrophilic material is applied to the hydrophobic porous substrate, the hydrophilic material contained in the coating liquid adheres to the hydrophobic porous substrate. Therefore, the coating amount of the hydrophilic material contained in the coating liquid can be said to be the adhesion amount of the hydrophilic material.
[0033] [Total heat exchange element] The total heat exchange element of the present invention is a total heat exchange element using the above-mentioned heat exchange element partition member of the present invention. That is, the total heat exchange element includes a plurality of the above-mentioned total heat exchange element partition members, and a spacing member arranged between the total heat exchange element partition members to maintain a spacing between the adjacent total heat exchange element partition members, and has a first air flow path formed by the total heat exchange element partition members and the spacing member provided thereon, and a second air flow path formed by the total heat exchange element partition members forming the first air flow path and the spacing member provided thereunder.
[0034] Hereinafter, the total heat exchange element will be described with reference to FIG. 1, however, the present invention is not limited to the total heat exchange element having the structure of FIG. Fig. 1 is a schematic diagram illustrating the structure of a total heat exchange element 10. As shown in Fig. 1, the total heat exchange element 10 is composed of a plurality of partition members 1 and a plurality of spacing members 2 that form air flow paths between the plurality of partition members 1 and maintain the spacing between the partition members 1. The partition members 1 are flat plates having a square, diamond, or other shape.
[0035] [Spacing member] The spacing member is not particularly limited as long as it maintains the distance between the partition members. The spacing member maintains the distance between the partition members, thereby forming an air flow path between the partition members. The spacing member 2 maintains the distance between the partition members 1, and is, for example, a corrugated plate shaped into a sawtooth or sinusoidal wave shape whose projected planar shape matches the shape of the partition member 1. The spacing member 2 is shaped, for example, like the core of a cardboard box, and is formed by corrugating.
[0036] The spacing member 2 is not limited to a corrugated material such as a paper substrate, film, or nonwoven fabric, but may be a resin rib. Among them, a paper substrate is preferable. Since a paper substrate has a moisture-regulating function, it can compensate for the decrease in the moisture-regulating function of a partition member using a hydrophobic porous substrate.
[0037] The ridges and valleys of the wave shape of the spacing member 2 are joined to the partition member 1 by an adhesive or the like. The spacing member 2 is joined to the partition member 1 on one surface of the partition member 1 with the direction of the wave shape ridges extending in a first direction (e.g., vertical direction), and is joined to the partition member 1 on the other surface with the direction of the wave shape ridges extending in a second direction (e.g., horizontal direction). That is, in two adjacent spacing members 2 sandwiching the partition member 1, the spacing members 2 are stacked alternately across the partition member 1 so that the direction of the wave shape ridges of the spacing member 2 joined to one surface, i.e., the first air flow path, is perpendicular to the direction of the wave shape ridges of the spacing member 2 joined to the other surface, i.e., the second air flow path.
[0038] Between the spacing member 2, whose corrugated ridge lines are oriented in a first direction (e.g., vertical direction), and the partition members 1 on both sides, a plurality of first air flow paths 4 are formed along the first direction. Furthermore, between the spacing member 2, whose corrugated ridge lines are oriented in a second direction (e.g., horizontal direction), and the partition members 1 on both sides, a plurality of second air flow paths 5 are formed along the second direction. Note that arrow 6 in Fig. 1 indicates the air flow direction in the first air flow path 4, and arrow 7 in Fig. 1 indicates the air flow direction in the second air flow path 5.
[0039] Since the spacing members 2 whose corrugated ridgelines are oriented in a first direction and the spacing members 2 whose corrugated ridgelines are oriented in a second direction are alternately stacked with the partition member 1 in between so that the ridgeline directions are perpendicular to each other, the first air flow path 4 and the second air flow path 5 are also alternately formed so that their extending directions are perpendicular to each other. For example, the first air flow path 4 is ventilated with supply air, and the second air flow path 5 is ventilated with exhaust air, and heat exchange takes place between the supply air and the exhaust air via the partition member 1 and the spacing members 2. 1, the spacing member 2 is provided so as to be perpendicular to the first air flow path and the second air flow path. However, it is not necessary to dispose the spacing member 2 so as to be perpendicular to the first air flow path and the second air flow path, and it is sufficient that the spacing members 2 are arranged in different directions, such as facing each other.
[0040] The method of joining the partition member and the spacing member can be a known method such as a method using an adhesive or a thermal bonding method without using an adhesive. Among them, the method using an adhesive is preferable because it can firmly bond the spacing member and the partition member. As the adhesive, a known adhesive such as a polyvinyl alcohol adhesive or an ethylene vinyl acetate adhesive can be used. EXAMPLES
[0041] The features of the present invention will be described in more detail below with reference to examples and comparative examples. The materials, amounts used, ratios, processing contents, processing procedures, etc. shown in the following examples can be appropriately changed without departing from the spirit of the present invention. Therefore, the scope of the present invention should not be interpreted as being limited by the specific examples shown below.
[0042] <Preparation of the substrate> Substrate A: A 20 μm thick polyethylene film (product name: SW320H, manufactured by Shenzhen Senior Technology Material Co., Ltd.) was prepared as a hydrophobic porous substrate. The surface density was 10.0 g / m 2 It was. Substrate B: A 16 μm thick polypropylene film (product name: SD216101+, manufactured by Shenzhen Senior Technology Material Co., Ltd.) was prepared as a hydrophobic porous substrate. The surface density was 9.4 g / m 2 It was.
[0043] Example 1 <Production of fine cellulose fiber A> (Phosphate group introduction step) The raw pulp used was softwood kraft pulp (solid content 93% by mass, basis weight 210 g / m) manufactured by Oji Paper Co., Ltd. 2 A sheet-like product (with a Canadian Standard Freeness (CSF) of 690 ml when disintegrated and measured in accordance with JIS P 8121:2012) was used. This raw pulp was subjected to phosphorylation treatment as follows. First, a mixed aqueous solution of ammonium dihydrogen phosphate and urea was added to the raw pulp to adjust the ratio of ammonium dihydrogen phosphate to 45 parts by mass, urea to 120 parts by mass, and water to 150 parts by mass per 100 parts by mass (bone dry mass) of raw pulp, to obtain a chemical-impregnated pulp. The chemical-impregnated pulp was then heated for 200 seconds in a hot air dryer at 165°C to introduce phosphoric acid groups into the cellulose in the pulp, to obtain a phosphorylated pulp.
[0044] (Cleaning process) The resulting phosphorylated pulp was then subjected to a washing treatment. The washing process was carried out by pouring 10 L of ion-exchanged water per 100 g (bone dry weight) of phosphorylated pulp, stirring to uniformly disperse the pulp, and then repeatedly filtering and dehydrating the pulp. The washing was completed when the electrical conductivity of the filtrate reached 100 μS / cm or less.
[0045] (Alkaline treatment process) Next, the washed phosphorylated pulp was subjected to an alkali treatment (neutralization treatment) as follows. First, the washed phosphorylated pulp was diluted with 10 L of ion-exchanged water, and then a 1N aqueous solution of sodium hydroxide was added little by little while stirring to obtain a phosphorylated pulp slurry having a pH of 12 to 13. Next, the phosphorylated pulp slurry was dehydrated to obtain phosphorylated pulp that had been subjected to an alkali treatment (neutralization treatment). Next, the phosphorylated pulp after the alkali treatment was subjected to the above-mentioned washing treatment. The infrared absorption spectrum of the phosphorylated pulp obtained after the alkali treatment was measured using FT-IR. -1 Absorption due to phosphate groups was observed in the vicinity, confirming that phosphate groups had been added to the pulp. In addition, the obtained phosphorylated pulp was analyzed using an X-ray diffraction device, and typical peaks for cellulose type I crystals were confirmed at two positions, around 2θ = 14° to 17° and around 2θ = 22° to 23°, confirming the presence of cellulose type I crystals.
[0046] (Fibrillation process) Ion-exchanged water was added to the phosphorylated pulp obtained through the above-mentioned alkali treatment process to prepare a slurry with a solid content concentration of 2% by mass. This slurry was treated three times at a pressure of 200 MPa in a wet pulverizer (Starburst, manufactured by Sugino Machine Co., Ltd.) to obtain a fine cellulose fiber dispersion liquid containing fine cellulose fiber A. X-ray diffraction confirmed that this fine cellulose fiber A maintained cellulose type I crystals. Furthermore, the fiber width of the fine cellulose fiber A was measured using a transmission electron microscope and found to be 3 to 5 nm. Furthermore, for the obtained fine cellulose fiber A,
[0047] <Manufacture of Partition Members for Total Heat Exchange Elements> To 99.2 parts of the 0.4% aqueous dispersion of the fine cellulose fibers A obtained above, 0.8 parts of a polyether surfactant (product name: SN Wet 985, manufactured by San Nopco, 76% aqueous dispersion) was added to prepare a coating liquid. The coating liquid was applied to one surface of the substrate A using a Mayer bar until the adhesion amount of the fine cellulose fibers A after drying was 0.12 g / m 2 The surface density of the partition member was 10.29 g / m. 2 It was.
[0048] Example 2 In Example 1, the substrate was changed to substrate B. Furthermore, the adhesion amount of the fine cellulose fibers A after drying was 0.25 g / m 2 A partition member for a total heat exchange element was obtained in the same manner as in Example 1, except that the surface density of the partition member was 9.89 g / m 2 It was.
[0049] Example 3 A partition member for a total heat exchange element was obtained in the same manner as in Example 1, except that the following was performed in Example 1.
[0050] <Production of fine cellulose fiber B> (Fibrillation process) Ion-exchanged water was added to the phosphorylated pulp obtained through the above-mentioned alkali treatment process to prepare a slurry with a solid content concentration of 2% by mass. This slurry was treated once with a wet pulverizer (Starburst, manufactured by Sugino Machine Co., Ltd.) at a pressure of 200 MPa to obtain a fine cellulose fiber dispersion liquid containing fine cellulose fiber B. X-ray diffraction confirmed that this fine cellulose fiber B maintained cellulose type I crystals. In addition, when the fiber width of fine cellulose fiber B was measured using a transmission electron microscope, it was confirmed that the fiber width was 3 to 500 nm.
[0051] <Manufacture of Partition Members for Total Heat Exchange Elements> The 0.4% dispersion of the fine cellulose fibers B obtained above was used as a coating liquid. One side of the substrate A was subjected to a corona discharge treatment, and then the coating liquid was applied to the substrate with a Mayer bar so that the adhesion amount of the fine cellulose fibers B after drying was 0.35 g / m 2 The surface density of the partition member was 10.35 g / m. 2 It was.
[0052] Comparative Example 1 In the production of the partition member for the total heat exchange element in Example 1, the adhesion amount of the fine cellulose fiber A after drying was 0.02 g / m 2 A partition member for a total heat exchange element was obtained in the same manner as in Example 1, except that the surface density of the partition member was 10.05 g / m 2 It was.
[0053] Comparative Example 2 The substrate A was used as it was as a partition member for the total heat exchange element.
[0054] Comparative Example 3 Substrate B was used as it was as a partition member for the total heat exchange element.
[0055] Example 4 A partition member for a total heat exchange element was obtained in the same manner as in Example 1, except that the following was performed in Example 1. <Manufacture of Partition Members for Total Heat Exchange Elements> The 0.5% aqueous dispersion of the fine cellulose fibers A obtained above was used as a coating liquid. The coating liquid was applied to one surface of the substrate A using a bar coater, and the substrate was dried at a dryer temperature of not more than 70° C. to obtain a partition member for a total heat exchange element. The amount of the fine cellulose fibers A attached was 0.05 g / m 2 The surface density of the partition material was 10.05 g / m 2 It was.
[0056] Example 5 A partition member for a total heat exchange element was obtained in the same manner as in Example 1, except that the following was performed in Example 1. <Manufacture of Partition Members for Total Heat Exchange Elements> To 99.6 parts of the 0.5% aqueous dispersion of the fine cellulose fibers A obtained above, 0.4 parts of a polyether surfactant (product name: SN Wet 985, manufactured by San Nopco, 76% aqueous dispersion) was added to prepare a coating liquid. The coating liquid was applied to one surface of the substrate A using a bar coater, and the substrate was dried at a dryer temperature of not more than 70° C. to obtain a partition member for a total heat exchange element. The amount of the fine cellulose fibers A attached was 0.15 g / m 2 The surface density of the partition material was 10.24 g / m 2 It was.
[0057] (evaluation) The moisture permeability and air permeability of the partition members for a total heat exchange element obtained in the examples and comparative examples are shown in Tables 1 and 2. In addition, for Examples 4 and 5 and Comparative Examples 2 and 3, the carbon dioxide barrier property was also evaluated. "Moisture permeability" Measurements were performed under conditions of 20°C and 65% RH in accordance with JIS Z0208:1976, with the following calculation formula: Moisture permeability=(a+b) / 2 Here, a = mass increment after 1 hour of measurement b = Mass increase per hour from 1 hour after the start of measurement to 2 hours after the start of measurement
[0058] "Air permeability" Measurements were taken in accordance with the Oken air permeability method of JAPAN TAPPI Paper and Pulp Test Method No. 5-2:2000.
[0059] <Carbon dioxide barrier properties> The measurement device consisted of a carbon dioxide (CO2) analyzer installed inside an acrylic cubic container measuring 1 m on each side, with square windows measuring 20 cm on each side in the center of each of the four side faces and the top face. With 25 cm square partition members attached to each window of the measuring device, 5,000 ppm of carbon dioxide was sealed in the container, and the CO2 concentration was measured four times every 15 minutes for a total of one hour under conditions of 20°C and 65% humidity. The rate of decrease in the carbon dioxide concentration at each time point is calculated from the measured values after 15 minutes, 30 minutes, 45 minutes, and 60 minutes, and the average is calculated to determine the rate of decrease in the carbon dioxide concentration of the measured sample. The lower the rate of decrease in the carbon dioxide concentration, the better the carbon dioxide (CO2) barrier property of the partition material. The partition member is preferably one having a carbon dioxide concentration reduction rate of 1.3% or less. The evaluation results are shown in Tables 1 and 2 below.
[0060] [Table 1]
[0061] [Table 2] [Explanation of symbols]
[0062] 1 Partition member 2 Spacing members 4 First air flow path 5 Second Air Flow Path 10 Total heat exchange element
Claims
1. A partition member for a total heat exchange element comprising a hydrophobic porous substrate and a hydrophilic material, the hydrophilic material is attached to the hydrophobic porous substrate; The thickness of the hydrophobic porous substrate is 5 μm or more and 30 μm or less, The amount of the hydrophilic material attached is 0.01 g / m 2 8g / m or more 2 is as follows: The surface density as a partition member for a total heat exchange element is 30 g / m 2 The following describes a partition member for a total heat exchange element having an air permeability of 10,000 seconds or more.
2. 2. The partition member for a total heat exchange element according to claim 1, wherein the hydrophobic porous substrate has an air permeability of 1000 seconds or less.
3. 2. The partition member for a total heat exchange element according to claim 1, wherein the hydrophilic material is applied to the hydrophobic porous substrate.
4. The moisture permeability of the partition member for the total heat exchange element is 2500 g / m 2 The partition member for a total heat exchange element according to claim 1, having a durability of 24 hours or more.
5. A heat exchanger according to any one of claims 1 to 4, a spacer member arranged between the total heat exchange element partition members and spaced apart from the adjacent total heat exchange element partition members; A total heat exchange element having a first air flow path formed by a partition member for the total heat exchange element and the spacing member provided thereon, and a second air flow path formed by a partition member for the total heat exchange element that forms the first air flow path and the spacing member provided below it.
6. A hydrophobic porous substrate having a thickness of 5 μm or more and 30 μm or less is provided with a hydrophilic material attached in an amount of 0.01 g / m on at least one surface thereof. 2 8g / m or more 2 The coating liquid containing the hydrophilic material is applied and dried so that the surface density is 30 g / m 2 The following describes a method for producing a partition member for a total heat exchange element having an air permeability of 10,000 seconds or more.
7. The method for producing a partition member for a total heat exchange element according to claim 6, wherein the hydrophobic porous substrate has an air permeability of 1000 seconds or less.
8. The moisture permeability of the partition member for the total heat exchange element is 2500 g / m 2 The method for producing a partition member for a total heat exchange element according to claim 6, wherein the duration is 24 hours or more.
9. The method for producing a partition member for a total heat exchange element according to any one of claims 6 to 8, wherein the coating liquid is applied by using any one of a blade coater, a bar coater, and a rod coater.
10. The method for producing a partition member for a total heat exchange element according to any one of claims 6 to 8, wherein the coating liquid is dried at a surface temperature of 80°C or lower.
11. The method for producing a partition member for a total heat exchange element according to any one of claims 6 to 8, wherein the coating liquid contains a surfactant.
12. The method for producing a partition member for a total heat exchange element according to any one of claims 6 to 8, wherein the coating liquid is applied to the hydrophobic porous substrate after the substrate is subjected to a surface hydrophilization treatment.
Citation Information
Patent Citations
Sheet containing derivative functional group-detached cellulose fine fibers
JP2019007101A
Thin film cellulose fine fiber laminate sheet
JP2019162818A
Sheet and manufacturing method for sheet
JP2020153023A
Manufacturing method of moisture permeable film for total heat exchange element
JP2022156537A
Sheet for total heat exchangers, element for total heat exchangers, and total heat exchanger
WO2019026823A1